Serous Otitis Media in Pre-School Children - Keramat Mozaffarinia; Yeganeh Teimouri; Afshin Sarrafinejad (Iranian Journal of Otorhinolaryngology, 2010)
Introduction: Salivary gland tumors are relatively rare and constitute 3-4% of all head and neck neoplasms. The majority (70%) of salivary gland tumors arise in the parotid gland. Recommended treatment for a parotid mass is surgical excision with a surrounding cuff of normal tissue to prevent recurrence. Materials and Methods: This is a retrospective study of 300 patients who were operated by a single surgeon for parotidectomy over a 20-year period in Ghaem Hospital, Mashhad, Iran. The patients' age, sex, operation findings, pathology report and type of surgery (parotidectomy or mastoidectomy) were analyzed. Results: In 25 cases we had to find the nerve in a retrograde fashion by finding the distal branches and dissecting backwards to reach the mass, whereas in 275 patients the trunk of the facial nerve was approached in a conventional antegrade fashion. Twelve cases needed some sort of repair on the nerve due to a trauma in the surgical field, either grafting or anastomosis was done. Interestingly mastoidectomy was required in 5 of our cases. The aim of these mastoidectomies was to eradicate the malignancy in cases where a perineural invasion was present. It also gave us a chance to find a normal proximal nerve ending in order to perform a safe nerve reconstruction (grafting or anastomosis). Conclusion: Mastoidectomy and facial nerve anastomosis may be required in parotid surgery.